Glutaminase-free L-asparaginase production by Leucosporidium muscorum isolated from Antarctic marine-sediment - Freire, Rominne Karla Barros; Mendonça, Carlos Miguel Nóbrega; Ferraro, Rafael Bertelli; Moguel, Ignacio Sánchez; Tonso, Aldo; Lourenço, Felipe Rebello; Santos, João Henrique Picado Madalena; Sette, Lara Durães [UNESP]; Pessoa Junior, Adalberto (Taylor & Francis, 2020)
L-asparaginase (ASNase) is an essential drug in the treatment of acute lymphoblastic leukemia (ALL). Commercial bacterial ASNases increase patient survival, but the consequent immunological reactions remain a challenge. Yeasts ASNase is closer to human congeners and could lead to lower side effects. Among 134 yeast strains isolated from marine-sediments in King George Island, Antarctica, nine were L-asparaginase producing yeasts and glutaminase-free. Leucosporidium muscorum CRM 1648 yielded the highest ASNase activity (490.41 U.L−1) and volumetric productivity (5.12 U.L−1 h−1). Sucrose, yeast extract and proline were the best carbon and nitrogen sources to support growth and ASNase production. A full factorial design analysis pointed the optimum media condition for yeast growth and ASNase yield: 20 g L−1 sucrose, 15 g L−1 yeast extract and 20 g L−1 proline, which resulted in 4582.5 U L−1 and 63.64 U L−1 h−1 of ASNase and volumetric productivity, respectively. Analysis of temperature, pH, inoculum and addition of seawater indicated the best condition for ASNase production by this yeast: 12–15 °C, pH 5.5–6.5 and seawater >25% (v/v). Inoculum concentration seems not to interfere. This work is pioneer on the production of ASNase by cold-adapted yeasts, highlighting the potential of these microbial resources as a source of glutaminase-free L-asparaginase for commercial purposes.
Keywords: Cold-adapted yeast; enzyme production; glutaminase-free asparaginase; L-asparaginase; Leucosporidium muscorum